Generalized Selection Method - Lovíšková, Jana; Pernecký, Daniel (Computing and Informatics, 2020)
In this paper we introduce new selection method, 3-selection method. This method tries to generalize the most used selection methods in Genetic Algorithms (GA). Our new method involves both proportional and rank-based methods (order-based) and, moreover, it allows scaling of selection pressure with higher precision. This method is based on defining the shape of probability density distribution which is adjustable by parameters of our method. In addition, our method has one more attribute which adds randomness of selection.